Konsep Bacaruik bagi Masyarakat Sumatera Barat - Azani, Gandhi Wira; Fikry, Zulian (Lembaga Yasin AlSys, 2025)
This study aims to explore the concept of bacaruik—a form of profanity in the Minangkabau language that includes vulgar references to female genitalia—as used in the daily life of communities in West Sumatra. Utilizing a qualitative approach grounded in Indigenous Psychology, data were collected through an open-ended online questionnaire completed by 176 native West Sumatran respondents (102 female, 74 male). Thematic analysis revealed that bacaruik is most frequently used as an outlet for emotional expression, particularly in situations of anger (80 respondents) and frustration (50 respondents), with 80.33% linking its usage to emotional contexts. Affectively, 60.67% reported experiencing negative emotions after using bacaruik, with the highest proportion among women (67.92%), while 24.71% felt relief or satisfaction, predominantly among men (33.33%). Although the majority (67.97%)—especially women (99.05%)—perceived bacaruik as useless, a minority (32.02%), almost entirely male, regarded it as beneficial for self-expression, strengthening social bonds, and defusing tension. These findings highlight a cultural paradox between Minangkabau customary norms, such as Kato nan Ampek, and everyday social practices. They also underscore bacaruik as a complex psychosociolinguistic phenomenon, reflecting the interplay of emotional dynamics, gender norms, and the negotiation of cultural values in contemporary society.